OakContigDF159.1, a reference library for studying differential gene expression in Quercus robur during controlled biotic interactions: use for quantitative transcriptomic profiling of oak roots in ectomycorrhizal symbiosis. Issue 2 (15th May 2013) - Tarkka, Mika T.; Herrmann, Sylvie; Wubet, Tesfaye; Feldhahn, Lasse; Recht, Sabine; Kurth, Florence; Mailänder, Sarah; Bönn, Markus; Neef, Maren; Angay, Oguzhan; Bacht, Michael; Graf, Marcel; et al.
Summary: Oaks ( Quercus spp.), which are major forest trees in the northern hemisphere, host many biotic interactions, but molecular investigation of these interactions is limited by fragmentary genome data. To date, only 75 oak expressed sequence tags (ESTs) have been characterized in ectomycorrhizal (EM) symbioses. We synthesized seven beneficial and detrimental biotic interactions between microorganisms and animals and a clone (DF159) of Quercus robur . Sixteen 454 and eight Illumina cDNA libraries from leaves and roots were prepared and merged to establish a reference for RNA‐Seq transcriptomic analysis of oak EMs with Piloderma croceum . Using the Mimicking Intelligent Read Assembly (MIRA) and Trinity assembler, the OakContigDF159.1 hybrid assembly, containing 65 712 contigs with a mean length of 1003 bp, was constructed, giving broad coverage of metabolic pathways. This allowed us to identify 3018 oak contigs that were differentially expressed in EMs, with genes encoding proline‐rich cell wall proteins and ethylene signalling‐related transcription factors showing up‐regulation while auxin and defence‐related genes were down‐regulated. In addition to the first report of remorin expression in EMs, the extensive coverage provided by the study permitted detection of differential regulation within large gene families (nitrogen, phosphorus and sugar transporters, aquaporins). This might indicate specific mechanisms of genome regulation in oak EMs compared with other trees. Abstract : See also the Commentary by Plomion and Fievet